Novel Biological Approaches for Testing the Contributions of Single DSBs and DSB Clusters to the Biological Effects of High LET Radiation - Mladenova, Veronika; Mladenov, Emil; Iliakis, George (Frontiers in Oncology, 2016)
The adverse biological effects of ionizing radiation (IR) are commonly attributed to the generation of DNA double-strand-breaks (DSBs). IR-induced DSBs are generated by clusters of ionizations, bear damaged terminal nucleotides and frequently comprise base damages and single strand breaks in the vicinity generating a unique DNA damage-clustering effect that increases DSB “complexity”. The number of ionizations in clusters of different radiation modalities increases with increasing linear-energy-transfer (LET), and is thought to determine the long-known LET-dependence of the relative biological effectiveness (RBE). Multiple ionizations may also lead to the formation of DSB-clusters comprising two or more DSBs that destabilize chromatin further and compromise overall processing. DSB complexity and DSB-cluster formation are increasingly considered in the development of mathematical models of radiation action, which are then “tested” by fitting available experimental data. Despite a plethora of such mathematical models the ultimate goal, i.e. the “a-priori” prediction of the radiation effect, has not yet been achieved. The difficulty partly arises from unsurmountable difficulties in testing the fundamental assumptions of such mathematical models in defined biological model systems capable of providing conclusive answers. Recently, revolutionary advances in methods allowing the generation of enzymatic DSBs at random or in well-defined locations in the genome, generate unique testing opportunities for several key assumptions frequently fed into mathematical modeling – including the role of DSB-clusters in the overall effect. Here, we review the problematic of DSB-cluster formation in radiation action and present novel biological technologies that promise to revolutionize the way we address the biological consequences of such lesions. We describe new ways of exploiting the I-SceI endonuclease to generate DSB-clusters at random locations in the genome and describe the possible utility of Zn-finger nucleases and of TALENs in generating DSBs at defined genomic locations. Finally, we describe ways to harness the revolution of CRISPR/Cas9 technology to advance our understanding of the biological effects of DSBs. Collectively, these approaches promise to improve the focus of mathematical modeling of radiation action by providing testing opportunities for key assumptions on the underlying biology. They are also likely to further strengthen interactions between experimental radiation biologists and mathematical modelers.